A slow-release defoaming type grafted modified silica material, a preparation method and application thereof

CN117402363BActive Publication Date: 2026-11-03JIANGSU SOBUTE NEW MATERIALS CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210796947.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-06
Publication Date
2026-11-03
Estimated Expiration
2042-07-06

AI Technical Summary

Technical Problem

Existing defoamers have strong defoaming ability in the early mixing stage of fresh concrete, which affects workability, resulting in uneven concrete quality and poor appearance after hardening. There is a lack of technology to control the air content of concrete in real time.

Method used

The method employs a slow-release defoaming grafted modified silica material. By grafting siloxane-containing modified monomers onto the surface of the silica material and combining them with long-chain alkyl alcohol polyethers, a defoamer is formed that slowly releases in an alkaline environment. This controls the air content of the concrete, ensuring workability by not defoaming initially, and gradually defoaming in the later stages to improve strength and appearance.

Benefits of technology

It improves the workability of fresh concrete and the strength and appearance of hardened concrete. By controlling the amount of air bubbles through slow-release defoamer, it enhances the durability and aesthetics of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure BDA0003732502080000021
    Figure BDA0003732502080000021
Patent Text Reader

Abstract

The application provides a slow-release defoaming grafted modified silica material capable of regulating the air content of concrete in real time, a preparation method and application. The material is made by connecting a siloxane group-containing modified monomer to the surface of the silica material through a silicon-oxygen bond; the siloxane group-containing modified monomer is composed of a siloxane group, an acid anhydride group and a long-chain alkyl alcohol polyether, and the acid anhydride group is connected to the siloxane group through an amide bond and connected to the long-chain alkyl alcohol polyether through an ester bond. The siloxane group-containing modified monomer is hydrolyzed under alkaline conditions to release the long-chain alkyl alcohol polyether with a defoaming function. The material added to the concrete can achieve no defoaming in the initial stage of concrete mixing, so that the fresh concrete has good workability, and slowly releases the defoaming agent in the later stage to reduce the air content in the concrete, thereby improving the strength and durability of the hardened concrete, and beautifying the appearance of the hardened concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a concrete admixture, specifically to a slow-release defoaming grafted modified silica material, its preparation method, and its application. Background Technology

[0002] Tiny, stable air bubbles in concrete can effectively improve its freeze-thaw durability and impermeability, while also significantly enhancing the workability of fresh concrete and eliminating segregation and bleeding. However, introducing too many unstable air bubbles can reduce the strength of hardened concrete. Furthermore, with economic development and rising public aesthetic standards, the requirements for the appearance of hardened concrete are increasing. Excessive large air bubbles can induce honeycomb-like pitting on the surface of hardened concrete, causing not only aesthetic defects but also shortening the lifespan of buildings. Therefore, to overcome honeycomb-like pitting on the concrete surface, improve the mechanical properties of concrete, and extend its service life, defoamers need to be added during the concrete pre-mixing process to eliminate excess air bubbles.

[0003] Defoamers are surfactants with specific hydrophilic-lipophilic balance (HLB) values. They diffuse at the gas-liquid interface of air bubbles, reducing surface tension and disrupting the mechanical balance of the gas-liquid interface, leading to bubble collapse and suppression. Many defoamers with novel structures have been developed (CN 109988301 A; CN109970894 A). However, these structures and traditionally used defoamers exhibit strong defoaming capabilities in the early mixing stages of fresh concrete, which is detrimental to its workability. Therefore, developing a novel defoamer with poor defoaming ability in the early mixing stages to ensure the workability of fresh concrete, while exhibiting strong defoaming ability in the later stages of mixing to produce a smooth and aesthetically pleasing hardened concrete surface, is of great significance.

[0004] At present, there are no reports on the research of novel concrete admixtures that use molecular design and chemical methods to organically combine inorganic materials with defoamer molecules to control air bubbles in real time in the field of concrete. Summary of the Invention

[0005] Although existing defoamers possess strong defoaming capabilities, they are not conducive to the workability of fresh concrete in the early mixing stages, leading to uneven concrete quality and consequently affecting building quality. To address this issue, this invention provides a slow-release defoaming grafted modified silica material capable of real-time control of concrete air content, its preparation method, and its application. Adding this slow-release defoaming grafted modified silica material to concrete prevents defoaming in the initial mixing stage, resulting in better workability of the fresh concrete. Later, it slowly releases the defoamer, reducing the air content in the concrete, thereby improving the strength and durability of the hardened concrete and enhancing its appearance.

[0006] The slow-release defoaming grafted modified silica material of this invention comprises a silica material surface with a siloxane-containing modified monomer linked by siloxane bonds. The siloxane-containing modified monomer is composed of a siloxane group, an anhydride group, and a long-chain alkyl alcohol polyether, wherein the anhydride group is linked to the siloxane group via an amide bond, and the anhydride group is linked to the long-chain alkyl alcohol polyether via an ester bond. Under alkaline conditions, the siloxane-containing modified monomer hydrolyzes to release the long-chain alkyl alcohol polyether, which has defoaming properties.

[0007] The particle size of the silica is in the range of 100nm-100um, and the molar ratio of silica to siloxane-modified monomer is 1:(5-50).

[0008] The monomer source of the siloxane is γ-aminopropyltriethoxysilane (KH550);

[0009] The monomer source of the anhydride group is any one of succinic anhydride, maleic anhydride, glutaric anhydride, and phthalic anhydride;

[0010] The monomer source of the long-chain alkyl alcohol polyether is a long-chain alkyl alcohol polyether defoamer, and its structural formula is as follows (Ⅰ):

[0011]

[0012] In formula (Ⅰ), m is the number of structural units of propylene oxide, which is an integer between 1 and 3; n is the number of structural units of ethylene oxide, which is an integer between 4 and 9; R is a straight-chain alkyl group containing 14 to 24 carbon atoms.

[0013] The general structural formula of the slow-release defoaming grafted modified silica material of the present invention is as follows: Formula (II):

[0014]

[0015] In formula (II), m is the number of structural units of propylene oxide, which is an integer between 1 and 3; n is the number of structural units of ethylene oxide, which is an integer between 4 and 9; R is a straight-chain alkyl group containing 14 to 24 carbon atoms.

[0016] X is selected from any one of -C2H4-, -CH=CH-, -C3H6-, and o-phenyl;

[0017] It is a monomer modified with siloxane. It is silica with surface grafted siloxane-modified monomers.

[0018] The preparation method of the slow-release defoaming grafted modified silica material of the present invention firstly modifies the surface of silica particles with a silane coupling agent to generate aminated silica, then grafts it with an acid anhydride to obtain carboxyl-modified silica, and finally the carboxyl-modified silica undergoes an esterification reaction with long-chain alkyl alcohol polyether defoamer molecules under the action of a catalyst to obtain the slow-release defoaming grafted modified silica material.

[0019] The mass ratio of silicon dioxide to silane coupling agent is 1:(1-2);

[0020] The mass ratio of aminated silica to acid anhydride is 1:(1.5-2.5);

[0021] The mass ratio of the carboxyl-modified silica to the defoamer is 1:(3-10);

[0022] The catalyst is one of p-toluenesulfonic acid, molecular sieve, 4-dimethylaminopyridine / N,N'-dicyclohexylcarboimide (DMAP / DCC), or 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride / N-hydroxysuccinimide (EDC / NHS); the amount of catalyst used is 0.05-0.2 times the mass of the carboxyl-modified silica particles.

[0023] The specific preparation method of the slow-release defoaming grafted modified silica material includes the following steps:

[0024] (1) Mix silica particles with γ-aminopropyltriethoxysilane in an ethanol / water mixture at a mass ratio of 1:(1-2) and then put them into a reaction vessel. Stir evenly, heat to 50-80℃, react for 1-2 hours, filter and wash, and dry in a drying oven to obtain aminated silica.

[0025] (2) Dissolve the aminated silica obtained in step (1) in an ethanol solution, then continuously add 1.5-2.5 times the amount of acid anhydride, stir at 30-40℃ for 2-3 hours, centrifuge to remove unreacted acid anhydride, and dry to obtain carboxyl-modified silica.

[0026] (3) Dissolve carboxyl-modified silica particles in an organic solvent, put them into a reactor equipped with a reflux device, add a catalyst, heat to 120-160℃, slowly add long-chain alkyl alcohol polyether defoamer, heat under reflux, react for 2-5 hours, cool down, remove the solvent by distillation, and dry to obtain slow-release defoaming grafted modified silica material.

[0027] The organic solvent is one of N,N-dimethylformamide (DMF) and toluene;

[0028] The basic synthetic route for the slow-release defoaming grafted modified silica material described in this invention is shown below, wherein... Silica particles with hydroxyl groups on their surface:

[0029]

[0030] The slow-release defoaming grafted modified silica material described in this invention is a powder. When using it, it should be mixed with cement and then combined with other conventional raw materials to form concrete. Because the single-molecule slow-release defoaming grafted modified silica material can release multiple defoamer molecules, the dosage of the powder material should not be too high. It is recommended that the dosage be 0.05-0.5% of the mass of the cementitious materials in the concrete.

[0031] Compared with traditional defoamers, the slow-release defoaming grafted modified silica material of this invention has the following beneficial effects:

[0032] 1. Slow-release defoaming grafted modified silica material is directly added to concrete. Initially, it does not have defoaming function. However, in the later stages, due to the change in the alkaline environment of cement, the ester bonds in the silica particles slowly hydrolyze, releasing long-chain alkyl alcohol polyethers to reduce the air content of the concrete. That is, the concrete does not defoam in the early stage of mixing, giving the fresh concrete good workability. In the middle and later stages, the long-chain alkyl alcohol polyethers gradually defoam, reducing the air content of the concrete, thereby improving the strength and durability of the concrete in the middle and later stages and beautifying the appearance of the hardened concrete.

[0033] 2. The carboxyl-modified silica residue left by the hydrolysis of slow-release defoaming grafted silica material can fill the micropores of hardened cement paste, further improving porosity and pore structure, and increasing the strength of concrete. At the same time, the carboxyl-modified silica particles are hydrophobically modified silica particles, which help the siloxane segments with weak defoaming function on their surface to contact the air bubbles, thereby doubly and efficiently improving the defoaming effect and thus increasing the strength of hardened concrete. Detailed Implementation

[0034] The following examples describe in more detail the preparation of slow-release defoaming grafted modified silica materials according to the method of the present invention. These examples are given by way of illustration and are intended to enable those skilled in the art to understand the content of the invention and implement it accordingly, but these examples do not limit the scope of the invention. All equivalent changes or modifications made according to the spirit and essence of the present invention should be covered within the protection scope of the present invention.

[0035] Synthesis Example 1

[0036] (1) 10g of silica with a particle size of 500nm and 10g of γ-aminopropyltriethoxysilane were mixed in an ethanol / water mixture and then added to a reaction vessel. The mixture was stirred evenly, heated to 60℃, reacted for 1h, filtered and washed, and dried in a drying oven to obtain aminated silica particles.

[0037] (2) Dissolve 10g of the obtained aminated silica in an ethanol solution, then continuously add 20g of succinic anhydride, stir at 35°C for 2h, centrifuge to remove unreacted anhydride, and dry to obtain carboxyl-modified silica particles.

[0038] (3) Dissolve 1g of carboxyl-modified silica particles in toluene and put them into a reactor equipped with a reflux device. Add 0.1g of p-toluenesulfonic acid, heat to 150℃, and then slowly add 6g of octadecyl alcohol defoamer (2PO,5EO). Heat to reflux and react for 3 hours. Then cool down, remove the solvent by distillation, and dry to obtain a slow-release defoaming grafted modified silica material with the structure shown in formula (Ⅲ) below.

[0039]

[0040] Synthesis Example 2

[0041] (1) 8g of silica with a particle size of 200nm and 10g of γ-aminopropyltriethoxysilane were mixed in an ethanol / water mixture and then added to a reaction vessel. The mixture was stirred evenly, heated to 70℃, reacted for 2h, filtered and washed, and dried in a drying oven to obtain aminated silica particles.

[0042] (2) Dissolve 10g of the obtained aminated silica in an ethanol solution, then continuously add 15g of maleic anhydride, stir at 40°C for 3h, centrifuge to remove unreacted anhydride, and dry to obtain carboxyl-modified silica particles.

[0043] (3) Dissolve 1g of carboxyl-modified silica particles in DMF and put them into a reactor equipped with a reflux device. Add 0.05g of molecular sieve, heat to 120℃, and then slowly add 3g of tetradecyl alcohol defoamer (3PO,4EO). Heat to reflux and react for 2 hours. Then cool down, remove the solvent by distillation, and dry to obtain a slow-release defoaming grafted modified silica material with the structure shown in formula (Ⅳ).

[0044]

[0045] Synthesis Example 3

[0046] (1) 5g of silica with a particle size of 1um and 10g of γ-aminopropyltriethoxysilane were mixed in an ethanol / water mixture and then added to a reaction vessel. The mixture was stirred evenly, heated to 50℃, reacted for 1.5h, filtered and washed, and dried in a drying oven to obtain aminated silica particles.

[0047] (2) Dissolve 10g of the obtained aminated silica in an ethanol solution, then continuously add 25g of glutaric anhydride, stir at 30°C for 2.5h, centrifuge to remove unreacted anhydride, and dry to obtain carboxyl-modified silica particles.

[0048] (3) Dissolve 1g of carboxyl-modified silica particles in toluene and put them into a reactor equipped with a reflux device. Add 0.185g of DMAP and 0.015g of DCC, heat to 160℃, and then slowly add 10g of docosyl alcohol defoamer (1PO,9EO). Heat to reflux and react for 5h. Cool down, remove the solvent by distillation, and dry to obtain a slow-release defoaming grafted modified silica material with the structure shown in formula (V).

[0049]

[0050] Synthesis Example 4

[0051] (1) 6g of silica with a particle size of 600nm and 10g of γ-aminopropyltriethoxysilane were mixed in an ethanol / water mixture and then added to a reaction vessel. The mixture was stirred evenly, heated to 80℃, reacted for 1h, filtered and washed, and dried in a drying oven to obtain aminated silica particles.

[0052] (2) Dissolve 10g of the obtained aminated silica in an ethanol solution, then continuously add 22g of phthalic anhydride, stir at 38°C for 3h, centrifuge to remove unreacted anhydride, and dry to obtain carboxyl-modified silica particles.

[0053] (3) Dissolve 1g of carboxyl-modified silica particles in toluene and put them into a reactor equipped with a reflux device. Add 0.15g of EDC and 0.03g of NHS, heat to 130℃, and then slowly add 8g of n-eicosyl alcohol defoamer (3PO,6EO). Heat to reflux and react for 4h. After cooling, remove the solvent by distillation and dry to obtain a slow-release defoaming grafted modified silica material with the structure shown in formula (VI).

[0054]

[0055] Comparative Example 1

[0056] Comparative Example 1 is the aminated silica particles obtained in Synthesis Example 1, whose structure is shown in Formula (VII).

[0057]

[0058] Comparative Example 2

[0059] Comparative Example 2 is the carboxyl-modified silica particles obtained in Synthesis Example 1, with the structure shown in formula (VIII).

[0060]

[0061] Comparative Example 3

[0062] Comparative Example 3 is a commercially available alkyl polyoxyethylene ether defoamer.

[0063] Application Examples

[0064] The application effect of the prepared slow-release defoaming grafted modified silica material was investigated through concrete tests. The slow-release defoaming grafted modified silica materials prepared in Synthetic Examples 1-4, as well as the admixtures in Comparative Examples 1-3, were used to test the air content and strength of concrete. The concrete mix proportions used are shown in Table 2.

[0065] Table 1 Concrete Mix Proportions

[0066] cement fly ash sand Dashi Xiaoshi water Polycarboxylate superplasticizer / adhesive 2.60kg 1.1kg 7.7kg 7.3kg 4.5kg 1.6kg 0.15wt%

[0067] The cement used was Jiangnan Onoda P·II 52.5 cement, the fly ash was Grade II fly ash, the sand was medium sand with a fineness modulus Mx = 2.7, and the aggregate was 5-20mm continuously graded crushed stone. The polycarboxylate superplasticizer and the long-chain alkyl alcohol polyether defoamer used in the synthesis example were provided by Jiangsu Subote New Material Co., Ltd. The slow-release defoaming grafted modified silica material of this invention was pre-mixed with the cement. The tests were conducted according to the relevant provisions of GB8076-2008 "Concrete Admixtures," and all defoamers were used at the same dosage, with a solid content of 0.8 parts per ten thousand of the binder material. The detailed method for determining the air content of concrete was performed according to GB 50080-2002 "Standard Method for Testing the Performance of Ordinary Concrete Mixtures," and the detailed method for determining the compressive strength of concrete was performed according to GB 50080-2002 and GB / T 50081-2002 "Standard Method for Testing the Mechanical Properties of Ordinary Concrete."

[0068] The experimental results are shown in Table 2. The blank group was concrete prepared according to the mix proportions in Table 1 without the addition of any defoamer. As can be seen from Table 2, the air content of the concrete in the blank group did not change much at the initial stage, 0.5h, 1h, and 2h. However, the air content of the concrete in Examples 1, 2, 3, and 4 decreased with the extension of time. At the beginning, the air content of the freshly mixed concrete was almost the same as that of the blank group. After 2h, the air content was significantly lower than that of the blank group and the comparative proportions. The slow-release defoaming effect of Example 1 was the most obvious. Moreover, comparing the 3d, 7d, and 28d strength data of the concrete, it was found that the compressive strength of the concrete in Examples 1, 2, 3, and 4 was higher than that of the blank group. This is because the slow-release defoaming grafted modified silica material has a slow-release function, which continuously releases alkyl polyoxyethylene ether defoaming components in an alkaline environment, thereby gradually reducing the air content of the concrete and enhancing the concrete strength.

[0069] Comparative Example 1 was prepared as an intermediate for the preparation of slow-release defoaming grafted modified silica material, which is aminated silica particles. It has no defoaming effect or a very weak defoaming effect. Therefore, the air content and compressive strength of concrete in Comparative Example 1 are basically the same as those in the blank group.

[0070] Comparative Example 2 is a carboxyl-modified silica particle intermediate for preparing a slow-release defoaming grafted modified silica material. It has the structure of a general defoamer, with hydrophobic chains and hydrophilic groups, and has a weak defoaming effect, but does not have a slow-release effect. Therefore, the initial air content of the concrete is reduced compared to Example 1, but its air content remains basically unchanged over time.

[0071] Comparative Example 3 is a commercially available alkyl polyoxyethylene ether defoamer. It also showed a significant defoaming effect on the initial stage of concrete but did not have a slow-release defoaming effect. Therefore, its air content dropped sharply in the initial stage, much lower than that of Example 1. However, its air content remained basically unchanged at all times, and after 2 hours, its air content was greater than that of Example 1. This is because the long-chain alkyl alcohol polyether and carboxyl modified silica released by the slow-release defoaming grafted silica material have a dual defoaming effect, which improves its defoaming function. Comparing the 3-day, 7-day, and 28-day strength data of concrete, it was found that the compressive strength of the concrete in Example 1 was significantly higher than that in Comparative Example 3, indicating that the slow-release defoaming grafted silica material of the present invention can improve the strength of hardened concrete while having good slow-release defoaming performance.

[0072] Table 2 Comparison of concrete test data between the examples and the comparative examples.

[0073]

[0074] The foregoing has shown and described the basic principles, main features, and advantages of this method. Those skilled in the art should understand that this method is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of this method. Various changes and modifications can be made to this method without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed method. The scope of protection of this method is defined by the appended claims and their equivalents.

Claims

1. A slow-release defoaming grafted modified silica material, characterized in that, A siloxane-modified monomer is attached to the surface of a silica material via siloxane bonds; the siloxane-modified monomer is composed of siloxane groups, anhydride groups, and long-chain alkyl alcohol polyethers, and the anhydride groups are attached to the siloxane groups via amide bonds and the anhydride groups are attached to the long-chain alkyl alcohol polyethers via ester bonds. The monomer of the long-chain alkyl alcohol polyether is derived from a long-chain alkyl alcohol polyether defoamer, and its structural formula is as follows (Ⅰ): (Ⅰ) In formula (Ⅰ), m is the number of structural units of propylene oxide, which is an integer between 1 and 3; n is the number of structural units of ethylene oxide, which is an integer between 4 and 9; R is a straight-chain alkyl group containing 14 to 24 carbon atoms. The particle size of the silica is in the range of 100nm-100um; The monomer source of the anhydride group is any one of succinic anhydride, maleic anhydride, glutaric anhydride, and phthalic anhydride.

2. The slow-release defoaming grafted modified silica material according to claim 1, characterized in that, The molar ratio of silicon dioxide to siloxane-modified monomer is 1:(5-50).

3. The slow-release defoaming grafted modified silica material according to claim 1, characterized in that, The monomer source of the siloxane is γ-aminopropyltriethoxysilane.

4. The slow-release defoaming grafted modified silica material according to claim 1, characterized in that, The general structural formula of the slow-release defoaming grafted modified silica material is as follows: (II) (Ⅱ) In formula (II), m is the number of structural units of propylene oxide, which is an integer between 1 and 3; n is the number of structural units of ethylene oxide, which is an integer between 4 and 9; R is a straight-chain alkyl group containing 14 to 24 carbon atoms. X is selected from any one of -C2H4-, -CH=CH-, -C3H6-, and o-phenyl; It is a monomer modified with siloxane. It is silica with surface grafted siloxane-modified monomers.

5. The method for preparing the slow-release defoaming grafted modified silica material according to any one of claims 1-4, characterized in that, First, the surface of silica particles is hydrophobically modified with a silane coupling agent to generate aminated silica, which is then grafted with anhydride to obtain carboxyl-modified silica. Finally, the carboxyl-modified silica undergoes an esterification reaction with long-chain alkyl alcohol polyether defoamer molecules under the action of a catalyst to obtain a slow-release defoaming grafted modified silica material. The mass ratio of silicon dioxide to silane coupling agent is 1:(1-2). The mass ratio of aminated silica to acid anhydride is 1:(1.5-2.5). The mass ratio of the carboxyl-modified silica to the defoamer is 1:(3-10).

6. The method according to claim 5, characterized in that, The catalyst is one of p-toluenesulfonic acid, molecular sieve, 4-dimethylaminopyridine / N,N'-dicyclohexylcarboimide (DMAP / DCC), or 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride / N-hydroxysuccinimide (EDC / NHS); the amount of catalyst used is 0.05-0.2 times the mass of the carboxyl-modified silica particles.

7. The method according to claim 6, characterized in that, The specific preparation method includes the following steps: (1) Mix silica particles with γ-aminopropyltriethoxysilane in an ethanol / water mixture at a mass ratio of 1:(1-2), then add the mixture to a reaction vessel, stir evenly, heat to 50-80℃, react for 1-2 hours, filter and wash, and dry in a drying oven to obtain aminated silica. (2) Dissolve the aminated silica obtained in step (1) in an ethanol solution, and then continuously add 1.5-2.5 times the amount of acid anhydride. Stir at 30-40℃ for 2-3 hours, centrifuge to remove unreacted acid anhydride, and dry to obtain carboxyl-modified silica. (3) Dissolve carboxyl-modified silica particles in an organic solvent, put them into a reactor equipped with a reflux device, add a catalyst, heat to 120-160℃, slowly add long-chain alkyl alcohol polyether defoamer, heat under reflux, react for 2-5 hours, cool down, remove the solvent by distillation, and dry to obtain slow-release defoaming grafted modified silica material.

8. The method according to claim 7, characterized in that, The organic solvent is one of N,N-dimethylformamide and toluene.

Citation Information

Patent Citations

  • Polymer concrete defoaming agent and preparation method and application thereof

    CN109970894A

  • Novel concrete defoaming agent, and preparation method and application thereof

    CN109988301A

  • Water-based foam control agent and preparation method thereof

    CN111514619A

  • Slow-release defoaming type nano-porous composite material as well as preparation method and application thereof

    CN114685089A